2010
DOI: 10.5194/acp-10-299-2010
|View full text |Cite
|
Sign up to set email alerts
|

Slower CCN growth kinetics of anthropogenic aerosol compared to biogenic aerosol observed at a rural site

Abstract: Abstract. Growth rates of water droplets were measured with a static diffusion cloud condensation chamber in MayJune 2007 at a rural field site in Southern Ontario, Canada, 70 km north of Toronto. The observations include periods when the winds were from the south and the site was impacted by anthropogenic air from the U.S. and Southern Ontario as well as during a 5-day period of northerly wind flow when the aerosol was dominated by biogenic sources. The growth of droplets on anthropogenic size-selected partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 63 publications
8
63
1
Order By: Relevance
“…[45] Some studies indicated that organic films could delay particle growth and thus influence detection of CCN [e.g., Ruehl et al, 2008;Shantz et al, 2010]. Comparison of droplet size spectra detected in the CCNC's optical particle counter for ambient aerosol and ammonium sulfate calibration aerosol gave no indication of strongly delayed growth in this study.…”
Section: Comparison To Previous Studiesmentioning
confidence: 78%
“…[45] Some studies indicated that organic films could delay particle growth and thus influence detection of CCN [e.g., Ruehl et al, 2008;Shantz et al, 2010]. Comparison of droplet size spectra detected in the CCNC's optical particle counter for ambient aerosol and ammonium sulfate calibration aerosol gave no indication of strongly delayed growth in this study.…”
Section: Comparison To Previous Studiesmentioning
confidence: 78%
“…CCN concentrations are not significantly affected, but even moderate particle concentrations can have an observable effect on droplet size (Lathem and Nenes, 2011). The second limitation of TDGA is that it cannot provide numerical values for vapor uptake coefficients; a droplet growth model such as those used by Shantz et al (2010), Ruehl et al (2008), Asa-Awuku et al (2009 and Kumar et al (2011a) is instead required.…”
Section: T Raatikainen Et Al: Activation Kinetics From Measurementsmentioning
confidence: 99%
“…Chuang, 2003Chuang, , 2006Sjogren et al, 2007;Drisdell et al, 2009;Tong et al, 2011) and supersaturated (e.g. Winkler et al, 2004Winkler et al, , 2006Ruehl et al, 2008Ruehl et al, , 2009Lance et al, 2009;Asa-Awuku et al, 2009Shantz et al, 2010) conditions have been used. Most of the latter are done with CCN instruments such as the Droplet Measurement Technologies (DMT) CCN counter (Lance et al, 2006), which is based on the Continuous Flow Streamwise Thermal Gradient Chamber (CFSTGC) design (Roberts and Nenes, 2005).…”
Section: T Raatikainen Et Al: Activation Kinetics From Measurementsmentioning
confidence: 99%
“…The optimal residence time can also depend on the aerosol chemical composition. This effect was not explored systematically during this study, although Shantz et al (2010) discuss the kinetics of activation during the Egbert 2007 study.…”
Section: Ccn Countermentioning
confidence: 99%